Multidisciplinary management of pregnancy-associated and early post-partum head and neck cancer patients - Bergamini, Cristiana; Cavalieri, Stefano; Resteghini, Carlo; Alfieri, Salvatore; Nuzzolese, Imperia; Colombo, Elena; Ottini, Arianna; Calareso, Giuseppina; Vingiani, Andrea; Iacovelli, Nicola Alessandro; Franceschini, Marzia; Guzzo, Marco; et al. (Frontiers in Oncology, 2023)
Background. Pregnancy-associated cancer (PAC) occurs during pregnancy or within 12 months after the delivery. Head and neck cancer (HNC) during pregnancy is infrequent, therefore diagnosis and personalized therapy are intricate.Methods. We investigated outcomes of 15 PAC patients (5 salivary, 4 nasopharyngeal, 3 thyroid, 2 oral cavity, one HPV-related carcinoma) diagnosed in the period 2005-2019. A literature review on PAC is provided.Results. Median gestational age at PAC diagnosis was 28 weeks (range: 16-40 weeks) in ten cases, at 5 months after delivery (range: 1 week-6 months) in the remaining five. Treatments included surgery (3 during pregnancy, 5 after childbirth), chemoradiation (8), and 3 patients with upfront metastatic disease received chemotherapy. Median survival was 6.6 years (eight women remain with no evidence of disease six years after diagnosis).2 This is a provisional file, not the final typeset article Conclusions. All patients received state-of-the-art therapy, with encouraging long-term results, highlighting treatment safety in women with HNC during pregnancy.